A critical analysis of benefits and challenges of implementing modular integrated construction. Issue 4 (12th March 2023) - Tsz Wai, Chan; Wai Yi, Pang; Ibrahim Olanrewaju, Oludolapo; Abdelmageed, Sherif; Hussein, Mohamed; Tariq, Salman; Zayed, Tarek
Abstract: Modular integrated construction (MiC) has recently been promoted by the advanced countries as an effective solution to 1) enable fast construction, 2) enhance the diminishing construction productivity, and 3) support sustainable development. In response to the COVID-19 pandemic, the completion of a MiC-based 1000-bed hospital in Wuhan, China, in less than a month, has made the world, especially sophisticated economies, 'talking' about this new technology. However, MiC is an ultra-modern technology that has both its merits and demerits; balancing out between them to maximize the opportunities that MiC has to offer needs insightful decision-making from higher authorities. Therefore, there is a vital need to understand and analyze the two contrasting but related matters, 'benefits and challenges of MiC' to help decision-makers in formulating better strategies based on informed choices. Past studies on MiC reported benefits in terms of time, cost, quality, safety, and environmental and social impacts, however, lack a holistic synthesis of MiC benefits by considering data from both the literature and real case studies. Whereas, the assessment methodologies used to prioritize MiC challenges did not consider the hierarchical nature of these challenges and their relative importance, which in turn impact the prioritization accuracy. This study contributed to bridging these gaps. Firstly, MiC benefits have been extensively explored by adopting a mixed research approach integrating literature synthesis, structured discussions, and real case studies. Then, a list of challenges was explored through literature synthesis and further validated and shortlisted through the first set of interviews from MiC experts. The second set of interviews was aimed mainly at evaluating the performance of MiC and providing recommendations for improvement from the international perspective. The interviews revealed that MiC should be treated as a long-term strategy and would not necessarily be a cheaper option in the short run, however, it would be a revolution in terms of time, quality, sustainability, safety, and life-cycle costs. Following the interviews, a questionnaire survey was conducted to prioritize the challenges using the multi-attribute group decision-making (MAGDM) approach, namely, Analytical Hierarchy Process (AHP), considering the hierarchical nature of challenges and their relative importance. The 'road network capacity' was found to be the most critical challenge. Finally, case studies were further carried out to reveal the measures that were adopted to mitigate the challenges in three international MiC projects. This research provides an interesting insight into the positive and negative aspects of using MiC for interested governments and construction stakeholders. It is anticipated that the benefits shall outweigh the drawbacks in the long run.